Pelatihan Produksi, Sanitasi dan Pemasaran Cokelat Praline Fungsional Bagi Ibu Rumah Tangga di Desa Cilebut Timur - Made Gayatri Anggarkasih; Andi Early Febrinda; Caecillia Chrismi Nurwitri; Tasya Nurfadila; Zaid Mustafa Kamil (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Cilebut Timur is one of the villages in Bogor Regency which is in Sukaraja District. Based on data in 2019, there were 15,987 people of which 7,852 were women and 3,286 were housewives. a total of 20 housewives in RW XIV, Cilebut Timur village, participated in training on the production, sanitation and marketing of functional praline chocolate. Participants directly practice making praline chocolate using fillings that have health values ​​such as pickled garlic, sesame, and koro beans so that praline chocolate is a functional food that is good for the body as well as a commercial product for entrepreneurship. After the activity, the participants had the desire to apply the skills given during the training and apply side businesses to improve family prosperity. Participants also assessed that overall this activity was very good in terms of responsiveness, empathy, tangible, reliability, assurance and continuity.